New cytotoxic protolimonoids from the stem bark of Aglaia argentea (Meliaceae). (September 2017) - Farabi, Kindi; Harneti, Desi; Nurlelasari,; Maharani, Rani; Hidayat, Ace Tatang; Awang, Khalijah; Supratman, Unang; Shiono, Yoshihito
Graphical abstract: Highlights: Two new protolimonoid, argentinin A (1 ) and B (2 ), were isolated from the stem bark of Aglaia argentea . The structures were determined based on 1D, 2D NMR and MS data. Argentinin A (1 ) and B (2 ) along with five known compounds (3–7 ) exhibited cytotoxic activity against P-388 murine leukimia cell lines. Abstract: Two new protolimonoid compounds, namely, argentinin A (1 ) and B (2 ) along with five known triterpenoid compounds, dammar-24-en-3α-ol (3 ), 3- epi -cabraleahydroxy lactone (4 ), ( E )-25-hydroperoxydammar-23-en-3β, 20-diol (5 ), mixture of eichlerianic acid and shoreic acid (6a and6b ), and dammar-24-en-3α, 20-diol (7 ), were isolated from the stem bark of Aglaia argentea . The structure of new compounds were elucidated by spectroscopic methods including one and two-dimensional NMR as well as high-resolution mass spectrometric analysis. All of the compounds were tested for their cytotoxic effects against P-388 murine leukemia cells in vitro . Among those isolated compounds, argentinin A (1 ) showed the strongest activity with an IC50 value of 1.27 μg/mL (3.05 μM).